2015
DOI: 10.1007/s12630-015-0376-1
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib pharmacogenetics and pediatric adenotonsillectomy: a double-blinded randomized controlled study

Abstract: BackgroundPediatric adenotonsillectomy (A&T) is associated with prolonged pain and functional limitation. Celecoxib is an effective analgesic in adult surgery patients; however, its analgesic efficacy on pain and functional recovery in pediatric A&T patients is unknown.MethodsDuring 2009-2012, children (age 2-18 yr) scheduled for elective A&T were enrolled in a single-centre double-blind randomized controlled trial. Study participants received either oral placebo or celecoxib 6 mg·kg−1 preoperatively, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 52 publications
(65 reference statements)
0
54
0
4
Order By: Relevance
“…Single nuclear polymorphisms for CYP2C9 are described and may contribute to clearance variability. Children given celecoxib with the genotype CYP2C9 *3 had less pain and improved functional recovery after tonsillectomy .…”
Section: Discussionmentioning
confidence: 97%
“…Single nuclear polymorphisms for CYP2C9 are described and may contribute to clearance variability. Children given celecoxib with the genotype CYP2C9 *3 had less pain and improved functional recovery after tonsillectomy .…”
Section: Discussionmentioning
confidence: 97%
“…The main issue in acute care is that coxibs do not inhibit platelet activity. They may be pro‐thrombotic in adult coronary and cerebrovascular disease but are an option for the child in pain post‐tonsillectomy or post haemophiliac bleed . As the renal effects of NSAIDs occur via a cox‐2 mechanism, it is essential that renal output is established before use.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al studied 60 children who were undergoing tonsillectomy or adenotonsillectomy and randomized to receive either parecoxib 1 mgÁkg -1 or saline at induction of anesthesia. The authors found that the saline group had significantly worse median Children's Hospital of Eastern Ontario Pain Scale pain scores (placebo, 9 [8-11] vs parecoxib, 7 [5][6][7][8]; P \ 0.001) in the postanesthesia care unit (PACU), needed more analgesic rescues with morphine (relative risk [RR], 1.5; 95% confidence interval [CI], 1.0 to 2.1; P = 0.024), needed rescue analgesics 61 min earlier (95% CI, 27 to 91; P = 0.001), and consumed 53% more overall morphine (P = 0.017). In addition, the saline group had more postoperative nausea and sedation (RR, 2.8; 95% CI, 1.0 to 7.7; P = 0.037).…”
mentioning
confidence: 99%
“…In the July 2015 issue of the Journal, Murto et al 5 published a similar and important study using celecoxib (also a COX-2 inhibitor) for the treatment of tonsillectomy pain in children ages two to 18 yr. Celecoxib is available in North America but not as an intravenous formulation. Children in the treatment group received 6 mgÁkg -1 of celecoxib orally preoperatively followed by 3 mgÁkg -1 twice daily for five doses.…”
mentioning
confidence: 99%
See 1 more Smart Citation